Subverting patriarchal narratives: a feminist approach to critical video game design through participatory methods - Torres-Parra, Carlos Roberto; Florez-Florez, Maria Juliana; Cuervo, Roberto; Ramírez-Pérez, Omar Fernando; Fonseca, Oscar (Frontiers in Sociology, 2025)
This article examines participatory design as a methodology for creating critical video games within the context of feminist pedagogy, focusing on the development of “Poder Violeta 2.” The game aims to challenge sexual harassment experienced by women, feminized bodies, and gender and sexual dissidents in Bogotá’s public transportation system, a context marked by some of the highest rates of insecurity for women. The design process for this new version prioritized the active involvement of women public transport users at all stages and enhanced the use of video game–specific resources, such as multiple playable characters and power-ups, to enrich gameplay and narrative depth. These strategies resulted in greater agency for the game’s protagonists and more accurate representation of historically marginalized groups. Qualitative transformations were observed both in the player experience and within the largely male development team, as the participatory process fostered ongoing learning and co-creation. The outcomes support the value of participatory design in generating inclusive and representative video game content, highlighting the narrative and pedagogical potential of medium-specific elements while emphasizing the empowerment and participation of historically excluded communities as a reference for future projects.